The Roles and Ways of Teachers in Motivating Students Studying English at Second Grade SMA n 1 Jambi Academic Year 2016/2017 - Riska Willianti; Wennyta Wennyta; Nurul Fitri (Universitas Batanghari Jambi, 2017)
AbstractThe background of this descriptive qaulitative study was to determine the Teacher’s Roles. It also aimed to find out how teacher’s roles in motivating students in studying English. This research was conducted at Second Grade SMA N 1 Jambi. The subject of this research was an English Teachers and also students at Second Grade of SMA N 1 Jambi. To collect data, the writed employed and questionnaire and interview techniques. The interview data used structured interview. The result of this research indicated that were kinds of Teacher’s roles that applied by English Teacher.Comparising:board,textbook,picture,recording, audio-visual media,laptop, and internet. Meanwhile, the audio-visual use for record the interview itself as the media selected by English Teacher. The key of teacher’s roles that used in order to motivate students in studying English.Keywords: Teacher’s Roles, Motivation, Studying English